Desenvolvimento do sensor baseado em eletrólito sólido de β-alumina para monitoramento de enxofre na indústria siderúrgica - Hasegawa, Haroldo Lhou (Universidade Federal de São Carlos, 2007)
Electrochemical sensors provide real time information of chemical compositions of molten metal. They can be used to improve the control of various metallurgical processes. One of the most successful and widely used electrochemical sensors is the oxygen sensor, based on zircônia solid electrolyte, usually used in steel making. Sensors are being developed for measurement of other chemical elements, but it is very costly and complicated to be produced. In order to solve this problem, in this work synthesis and assembly of β-alumina and β-alumina based on solid electrolyte sensors were studied. For this, the phase of interest was prepared by the mixing of oxides, and characterized. Traditional ceramic forming processes, isostatic and slip casting, were used to produce the prototypes and their ceramic characteristics were evaluated. Both compositions did not present high density after sintering at 1600°C, reaching 90% theoretical density. This fact could be responsible for the break down during the application of the sensors. The Na-β- alumina sensor produced did not present a satisfactory performance for measuring the dissolved sulphur in liquid pig iron. On the other hand, the β-alumina sensor, despite of the secondary phase, showed good behavior in terms of response time (between 5 and 8 seconds) for measuring the dissolved sulphur in liquid pig iron at temperatures from 1440°C to 1460°C, with La2O2SO4 auxiliary electrode and three different reference electrodes. The signal response of EMF between 54 mV and 174 mV was measured in a measuring level from 32 ppm (weight) to 432 ppm (weight) of sulphur dissolved on the metal bath
Development of ceramic solid electrolyte sensor based on β-alumina for sulphur monitoring in steelmaking industry
Keywords: Material cerâmico; Eletrólito sólido; Indústria siderúrgica; Monitoramento de enxofre; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA